PENGEMBANGAN DESAIN MEDIA PEMBELAJARAN BERBASIS GOOGLE SITES KEPADA GURU PADA PEMBELAJARAN DARING DI SMP ISLAM HARAPAN IBU JAKARTA-SELATAN - Setiawan, Kukuh; Nomi, Ahmad Suryadi; Winata, Widia (Instruksional, 2022)
ABSTRACTGoogle sites is one of the web site media that can be used in the learning process, group or personal. The purpose of this study is to find out: 1) Develop a design of learning media based on google sites in online learning, 2) How is the feasibility of designing learning media based on google sites in online learning. 3) How effective is the design of learning media based on google sites in online learning. 4) What is the potential effect of using google sites-based learning media design on online learning. The research approach used in this research is Research and Development (RnD). The results of this study are the development of online learning based on Google Sites based on the ADDIE model and declared "FEASIBLE". This is evidenced by several research results, namely the results of Media Expert Validation, Initial Field Trials, and Field Implementation Tests, the ability of teachers so far to be able to create and develop online learning media designs, online learning media based on Google Sites so far are acceptable Learners easily, practically and effectively whenever and wherever. Recommendations for schools or teachers are advised to be able to take advantage of online learning media based on google sites properly so that students can follow technological developments that are used for learning activities. Both learning in junior high school and learning at the next level, for future researchers who will develop online learning based on google sites, it is recommended to follow technological developments according to what the school has, such as the development of online learning based on Google Sites based on Google Sites so that variations in information delivery are more diverse.ABSTRAKGoogle sites adalah salah satu media webstite yang bisa dimanfaatkan dalam proses pembelajaran,kelompok ataupun pribadi. Tujuan penelitian ini adalah mengetahu: 1) Mengembangkan desain media pembelajaran berbasis google sites pada pembelajaran daring, 2) Bagaimana kelayakan desain media pembelajaran berbasis google sites pada pada pembelajaran daring. 3) Bagaimana keefektifan desain media pembelajaran berbasis google sites pada pada pembelajaran daring. 4) Bagaimana efek potensial penggunaan desain media pembelajaran berbasis google sites pada pembelajaran daring. Pendekatan penelitian yang digunakan dalam penelitian ini adalah Research and Development (RnD). Hasil penelitian ini yaitu Pengembangan pembelajaran daring berbasis Google Site berdasarkan model ADDIE dan dinyatakan “LAYAK”. Hal tersebut dibuktikan dengan beberapa hasil penelitian yaitu hasil Validasi Ahli Media, Uji Coba Lapangan Awal, dan Uji Pelaksanaan Lapangan., Kamampuan Guru sampai sejauh ini sudah dapat membuat dan mengembangkan design media pembelajaran secara daring, Media pembelajaran daring berbasis Google Site sejauh ini dapat diterima Peserta didik secara mudah, praktis dan efektif kapanpun dan dimanapun. Rekomendasi bagi sekolah atau Bapak/Ibu Guru disarankan untuk dapat memanfaatkan media pembelajaran daring berbasis google sites dengan baik agar Peserta didik dapat mengikuti perkembangan teknologi yang dimanfaatkan untuk kegiatan pembelajaran. Baik pembelajaran di Sekolah Menengah Pertama maupun pembelajaran di tingkatan berikutnya, Bagi peneliti berikutnya yang akan mengembangkan pembelajaran daring berbasis google sites disarankan untuk mengikuti perkembangan teknologi sesuai yang sekolah miliki seperti pengembangan pembelajaran daring berbasis Google Site berbasis Google Site agar variasi penyampaian informasi lebih beragam